Quantification of Noncovalent Interactions in Azide–Pnictogen, –Chalcogen, and –Halogen Contacts. Issue 14 (8th February 2021) - Bursch, Markus; Kunze, Lukas; Vibhute, Amol M.; Hansen, Andreas; Sureshan, Kana M.; Jones, Peter G.; Grimme, Stefan; Werz, Daniel B.
Abstract: The noncovalent interactions between azides and oxygen‐containing moieties are investigated through a computational study based on experimental findings. The targeted synthesis of organic compounds with close intramolecular azide–oxygen contacts yielded six new representatives, for which X‐ray structures were determined. Two of those compounds were investigated with respect to their potential conformations in the gas phase and a possible significantly shorter azide–oxygen contact. Furthermore, a set of 44 high‐quality, gas‐phase computational model systems with intermolecular azide–pnictogen (N, P, As, Sb), –chalcogen (O, S, Se, Te), and –halogen (F, Cl, Br, I) contacts are compiled and investigated through semiempirical quantum mechanical methods, density functional approximations, and wave function theory. A local energy decomposition (LED) analysis is applied to study the nature of the noncovalent interaction. The special role of electrostatic and London dispersion interactions is discussed in detail. London dispersion is identified as a dominant factor of the azide–donor interaction with mean London dispersion energy‐interaction energy ratios of 1.3. Electrostatic contributions enhance the azide–donor coordination motif. The association energies range from −1.00 to −5.5 kcal mol −1 . Abstract : The interactions that bind : The noncovalent interactions between azides and oxygen‐containing moieties are investigated through a computational study based on experimental findings. A set of 44 high‐quality, gas‐phase computational model systems with intermolecular azide–pnictogen, –chalcogen, and –halogen contacts are compiled and investigated through semiempirical quantum mechanical methods, density functional approximations, and wave function theory.